Faktor Penghambat Kerjasama Indonesia-Norwegia dalam Implementasi Redd+ Tahun 2011-2016 - Chayani, Ita Sabilah Putri; Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2022)
ABSTRACTEnvironmental issues are currently receiving a lot of attention worldwide, so they are widely discussed on international agendas. Many countries are starting to care about the sustainability of their country along with the sustainability of the environment in their territory. Some of these countries are Indonesia and Norway. Cooperation between Norway and Indonesia was carried out in the REDD+ program, which was built to significantly reduce greenhouse gas emissions due to deforestation and forest degradation. This research is qualitative with a descriptive method, with data collection techniques using literature, and the data used is secondary data. The result of this research is that there are social, environmental, and economic obstacles to implementing REDD+ in Indonesia, which has caused REDD+, which should have been completed in 2016, to continue to this day.Keywords: Environmental Issues, Collaboration, Deforestation, Degradation, ObstaclesDOI: https://doi.org/10.33005/jgp.v10i02.3749